2021
DOI: 10.1177/20322844211028304
|View full text |Cite
|
Sign up to set email alerts
|

Opening Pandora’s box: The right to silence in police interrogations and the Directive 2016/343/EU

Abstract: This article examines the provisions of the Directive 2016/343 related to the right to remain silent with special emphasis on pre-trial proceedings and police interrogations. It focuses on the inherent contradictions and unclarities of the respective provisions, particularly when interpreted in light of the respective ECtHR case law. The article also identifies areas, relevant to regulation of suspect interrogations and the right to silence, which are not addressed in the Directive or the ECtHR jurisprudence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The Irish Department of Justice appears to believe that the existence of Ireland's legislative inferences makes it impossible for the state to fulfil the terms of Directive 2012/ 13/EU (Daly, 2021), but this is not without question. Commentators (Pivaty et al 2021) have observed that the final wording of Directive 2012/13/EU allows for a number of possible interpretations such that its asserted prohibition on the use of adverse inference might not be as definitive as originally foreseen when the Directive was first considered. In discussing the need to continue those provisions in operation the Irish Minister for Justice and Equality stated in 2019 that such provisions are 'a key tool in the investigation and prosecution of serious crime' 41 (Daly, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Irish Department of Justice appears to believe that the existence of Ireland's legislative inferences makes it impossible for the state to fulfil the terms of Directive 2012/ 13/EU (Daly, 2021), but this is not without question. Commentators (Pivaty et al 2021) have observed that the final wording of Directive 2012/13/EU allows for a number of possible interpretations such that its asserted prohibition on the use of adverse inference might not be as definitive as originally foreseen when the Directive was first considered. In discussing the need to continue those provisions in operation the Irish Minister for Justice and Equality stated in 2019 that such provisions are 'a key tool in the investigation and prosecution of serious crime' 41 (Daly, 2021).…”
Section: Discussionmentioning
confidence: 99%
“… 9 On the operation and impact of Directive 2016/343/EU on the strengthening of certain aspects of the presumption of innocence and of the right to be present at the trial in criminal proceedings see further Pivaty et al (2021).…”
mentioning
confidence: 99%
“…Hoewel overeenkomstig de Richtlijn (EU) 2016/343 geen negatieve gevolgen mogen worden gekoppeld aan de uitoefening van deze rechten, kan dit toch een aantal onbedoelde neveneffecten teweegbrengen, waarbij politieambtenaren de uitoefening ervan (onbewust) kunnen beschouwen als een teken van liegen, niet willen meewerken en/of een indicatie van schuld. Dit is gebleken uit een door de Europese Unie gefinancierd onderzoek, waarbij op basis van een juridische analyse en kwalitatief empirisch onderzoek (interviews) het zwijgrecht in België, Italië, Nederland en Ierland werd onderzocht ('Emprise': Daly et al, 2022;Pivaty, Beazley, Daly, Beckers, et al, 2021;.…”
Section: De Rol Van Psychologische Mechanismen In Hoofde Van De Verda...unclassified